2013
DOI: 10.1007/s11427-013-4548-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane nanotubes: Novel communication between distant cells

Abstract: The many kinds of cell structures involved in cell-cell communication include tight junction, adherens junction and gap junction, but almost all are between adjacent cells. Recently, a general and dynamic membrane tether, termed tunneling nanotubes or membrane nanotubes (MNTs), was discovered to be involved in communication between distant cells. By facilitating intercellular communication, MNTs contribute to many biological functions and pathologic changes in cells. Many works have revealed the structure, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Although TNTs are present in the healthy cells, pathological conditions (e.g. infectious state, cancer) were previously associated with an increase in the number of TNTs 21 22 . TNTs represent an interesting feature of cells, which, generally, is related to the transfer of information between the two neighboring cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although TNTs are present in the healthy cells, pathological conditions (e.g. infectious state, cancer) were previously associated with an increase in the number of TNTs 21 22 . TNTs represent an interesting feature of cells, which, generally, is related to the transfer of information between the two neighboring cells.…”
Section: Resultsmentioning
confidence: 99%
“…As a hypothesis, alpha-syn may enter mitochondria to Bpull^them out in an actomyosin-dependent way [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the cell dislodgment mechanism may be typical for motile cells which include immune cells (e.g. macrophages or lymphocytes) (Chauveau et al 2010, Zhang & Zhang 2013). It is unclear what induces TNT formation but studies have shown that longer duration of cell-cell contact prior to separation increases TNT formation in T lymphocytes and NK cells (Chauveau et al 2010, Sowinski et al 2011, Sowinski et al 2008).…”
Section: Tunneling Nanotubes (Tnts)mentioning
confidence: 99%